2009
DOI: 10.1590/s0004-282x2009000100009
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea (OSA) and depressive symptoms

Abstract: -Background:The relationship between obstructive sleep apnea (OSA) and depressive symptoms is ambiguous in the literature. Purpose: To investigate if there is a correlation between depressive symptoms and the severity of OSA. Method: A retrospective, cross-sectional study of data from 123 consecutive adults patients with neither mental illness nor psychotropic drugs intake, referred to a sleep laboratory for an evaluation of OSA. For the statistical analysis (uni-and multivariate), we used the following variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
1
13
0
2
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18][19][20] Several explanations for the differences in these observations are possible. Firstly, it could be suggested that sleep apnea affects mood differently in people who are aware of their sleep apnea and that this difference might explain the conflicting results between studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16][17][18][19][20] Several explanations for the differences in these observations are possible. Firstly, it could be suggested that sleep apnea affects mood differently in people who are aware of their sleep apnea and that this difference might explain the conflicting results between studies.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 One study in patients with sleep apnea suggest that there is an association of low oxygen saturation with depressive symptoms but not between the apnea hypopnea index (AHI) with depressive symptoms, 14 whereas other studies suggest no association between indicators of sleep apnea severity with depressive symptoms. [15][16][17] A study including persons with suspected sleep apnea reported no consistent association between the severity of respiratory disturbances and depressive symptoms. 18 This is in line with results obtained from a large study of the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Macey et al, [25] in a population of 49 people with severe OSA and low comorbidities, found no association between the depressive symptoms assessed with the BDI and OSA severity. Also, Dominici and Gomes, [26] in a study of 123 cases referred to the sleep laboratory, showed a slightly significant association in the univariate analysis between the AHI and BDI scores. This association was no longer significant in the multivariate analysis when other variables were included, such as ESS score, BMI, comorbidity, age, and gender.…”
Section: Discussionmentioning
confidence: 92%
“…Studies reported different prevalence of OSA-caused depression ranging from 6% to 54% (7, 8). However, some of the studies could not find an association between depression and OSA (10-12). Depression and OSA are two common entities with health complications.…”
Section: Introductionmentioning
confidence: 96%